Prioritization factors of Enterprise Application Integration (EAI) adaption in Malaysia e-Government / Mazni Sohimi - Sohimi, Mazni (2021)
This dissertation examines the prioritization factors that can influence Enterprise Application Integration (EAI) adoption in Malaysian Government. This research focuses on Human Resource Management Information System (HRMIS) application which has been selected as the case study for this research. The analysis is divided into two parts. The first part is by analyzing the prioritization factors by using Analytic Hierarchy Process (AHP) technique while the second part is through multiple case study and document analysis. The study of these factors in these two parts is based on EAI adoption model that proposed by Kamal et al. (2009) and being compared to get the outcome. The results are comprised through a series of tables and one propose framework. Based on the outcomes, it illustrate that ten factors can be classified as most priority factors which must be considered when adopting EAI. Therefore, resulting in this research will guide Malaysian public sector to make a decision before proceeding with EAI adoption in e-Government project.